(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The study explores the intercultural pragmatics of English phraseological units, with particular attention to idioms and their functions in cross-cultural communication and translation. Idioms, as culturally embedded expressions, present significant challenges in interpretation and transfer, often leading to semantic shifts and pragmatic mismatches when translated into other languages. This research combines comparative analysis of English idioms with their Russian and Uzbek equivalents, corpus-based investigation of idiomatic use in discourse, and pragmatic evaluation of their communicative functions. Findings indicate that literal translations frequently result in semantic distortion, while functional equivalents preserve both meaning and pragmatic value more effectively. Moreover, descriptive paraphrasing, though semantically accurate, tends to reduce idiomaticity and cultural resonance. The study highlights the necessity of pragmatic awareness in both language learning and translation practices, underscoring that phraseological competence is an essential component of intercultural communication. By examining idioms as discourse units rather than isolated lexical items, this research contributes to a deeper understanding of how cultural values are embedded in language and how phraseological adaptation shapes modern communicative practices. The results have pedagogical implications for English as a foreign language instruction in Uzbekistan and beyond, as well as practical applications in translation studies, where preserving pragmatic equivalence remains a central challenge.